Tumor microenvironment in non-melanoma skin cancer resistance to photodynamic therapy - Cerro, Paulina A.; Mascaraque, Marta; Gallego-Rentero, María; Almenara-Blasco, Manuel; Nicolás-Morala, Jimena; Santiago, Juan Luis; González, Salvador; Gracia-Cazaña, Tamara; Juarranz, Ángeles; Gilaberte, Yolanda (Frontiers in Oncology, 2022)
Non-melanoma skin cancer has recently seen an increase in prevalence, and it is estimated that this grow will continue in the coming years. In this sense, the importance of therapy effectiveness has increased, especially photodynamic therapy. Photodynamic therapy has attracted much attention as a minimally invasive, selective and repeatable approach for skin cancer treatment and prevention. Although its high efficiency, this strategy has also faced problems related to tumor resistance, where the tumor microenvironment has gained a well-deserved role in recent years. Tumor microenvironment denotes a wide variety of elements, such as cancer-associated fibroblasts, immune cells, endothelial cells or the extracellular matrix, where their interaction and the secretion of a wide diversity of cytokines. Therefore, the need of designing new strategies targeting elements of the tumor microenvironment to overcome the observed resistance has become evident. To this end, in this review we focus on the role of cancer-associated fibroblasts and tumor-associated macrophages in the resistance to photodynamic therapy. We are also exploring new approaches consisting in the combination of new and old drugs targeting these cells with photodynamic therapy to enhance treatment outcomes of non-melanoma skin cancer.